Cognitive Behavioral Therapy for Anxiety Reduction Among Justice-Involved Youth: Insights from a Systematic Review - Amalia Choirunnisa; Mustikasari; Giur Hargiana (Talenta Publisher, 2025)
Teens involved in the juvenile justice system are particularly vulnerable to anxiety disorders due to recurrent exposure to adverse experiences and lack of psychological support. This systematic review aimed to evaluate the efficacy and implementation of Cognitive Behavioral Therapy (CBT) for reducing anxiety among justice-involved adolescents across diverse international contexts. Comprehensive searches were conducted across PubMed, Scopus, PsycINFO, ScienceDirect, and Google Scholar for studies published up to August 2025 involving adolescents aged 10–18 with experience in juvenile justice settings. Cohort, quasi-experimental, randomized controlled trials (RCTs), and pre–post intervention designs were included, and methodological quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal tools. Ten studies across the US, Germany, Nigeria, Turkey, Thailand, China, and Sweden met the inclusion criteria. Most reported significant reductions in anxiety, particularly in group-based or trauma-focused CBT interventions. Protocol adherence, practitioner skill, and cultural adaptation were identified as critical success factors, while implementation challenges included resource limitations and staff turnover. In conclusion, CBT demonstrates robust potential as an effective and adaptable intervention for anxiety reduction among justiceinvolved youth, especially when culturally tailored and trauma-informed. Further studies should focus on long-term outcomes and context-specific adaptation for resource-limited settings such as Indonesia. Keyword: Cognitive Behavioral Therapy, Anxiety Disorders, Juvenile Delinquency, Adolescent, Psychological Trauma